Study of deuterium plasma interaction with a tungsten target within RPI-IBIS facility - Skladnik-Sadowska, E.; Malinowski, K.; Sadowski, M.J.; Czaus, K.; Kubkowska, M.; Ladygina, M.S.; Sartowska, B. (Вопросы атомной науки и техники, 2008)
The paper presents results of experimental research on the interaction of a pulsed plasma-ion stream with a tungsten (W) target. The pulsed deuterium plasma was produced within the RPI-IBIS (Multi-Rod Plasma Injector) facility at IPJ in Swierk. Measurements were carried out by means of optical spectroscopy and corpuscular diagnostic techniques. Structural changes in the irradiated targets were investigated with a SEM. Before experiments with the W-target there were determined operational conditions, when clean deuterium plasma streams can be generated. For that purpose a so-called “slow or PID (Plasma Ion Deposition) mode” of the RPI-IBIS operation was chosen. Particular attention was paid to the identification of spectral lines from WI and WII species. The obtained results, i.e. optical spectra and other characteristics have demonstrated applicability of the RPI-IBIS facility for research on the interaction of plasma streams with W-targets, e.g. those constituting some internal parts of fusion facilities. Представлено результати експериментальних досліджень по взаємодії імпульсного плазмово-іонного потоку з вольфрамовою мішенню. Імпульсні дейтерієві потоки плазми генерувались в СПІ-ІБІС (стержневий плазмовий інжектор), який знаходиться в ІЯП у Шверку. Виміри проводились за допомогою оптичної спектроскопії та корпускулярної діагностики. Структурні зміни облучаємої мішені досліджувались за допомогою SEM. Перед експериментами з вольфрамовою мішенню визначались робочі умови, коли генерувались чисті дейтерієві плазмові потоки. Був вибраний так званий режим “повільний або PID-моди” (плазмового іонного осадження). Частична увага приділялась ідентифікації спектральних ліній WI та WII. Отримані результати, оптичні спектри та інші характеристики, продемонстрували можливість застосовувати установку СПІ-ІБІС для досліджень взаємодії плазмових потоків з W-мішенню, які складають деякі внутрішні частини термоядерного реактору. Представлены результаты экспериментальных исследований по взаимодействию импульсного плазменно-ионного потока с вольфрамовой мишенью. Импульсные дейтериевые потоки плазмы генерировались внутри СПИ-ИБИС (стержневой плазменный инжектор), который расположен в ИЯП в Шверке. Измерения проводились с помощью оптической спектроскопии и корпускулярной диагностики. Структурные изменения облучаемой мишени исследовались с помощью SEM. Перед экспериментами с вольфрамовой мишенью определялись рабочие условия, когда генерировались чистые дейтериевые плазменные потоки. Для этой цели был выбран так называемый режим “медленной или PID-моды” (плазменного ионного осаждения). Частичное внимание уделялось идентификации спектральных линий WI и WII. Полученные результаты, оптические спектры и другие характеристики, продемонстрировали применимость установки СПИ-ИБИС для исследований взаимодействия плазменных потоков с W-мишенью, которые составляют некоторые внутренние части термоядерного реактора.